Pkm Kelompok Nelayan Pengolah Ikan Pari Asap - Harlina, Harlina; Hadijah, Sitti (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
Stingray is a fish that is non-economical and less delicious when it is consumed fresh, but when it is processedby fogging, then the taste will be very delicious and popular among the community.So the smoked stingray is one of thetypical and popular products in Jeneponty regency. The processing of smoked stingrays in Jeneponto Regency is locatedin ToreangSubdistrict, namely